Survey dan Checklist Kesiapan Pasar Ber-SNI untuk Pasar Rakyat di Kota Pontianak (Bersama Dinas Koperasi, Usaha Mikro dan Perdagangan Kota Pontianak): Survey Pasar Ber-SNI - Kurniasih, Ninik; Siwi, Theresia; Sawitri, Sari; Yuliana, Elsa Sari; Arianto, Arianto; Soraya, Soraya; Kurnia, Ika; Wahyudi, Wahyudi; Al Farizi, Zulham (Kapuas, 2024)
To create the modern concept, the Indonesian government of Dinas Koperasi, Usaha Mikro dan Perdagangan Kota Pontianak, issue that the market conditions is most worthy SNI certified. Stipulated in the binding by SNI 8152 : 2015 that public market must have competitiveness to improve economic conditions. In SNI 8152 : 2015 mentioned that some markets can reach SNI label for 3 on fulfillment of requirements, namely: general terms, technical requirements and requirements management.The general requirements in terms of hygiene, health, security, and comfort. While zoning in the form of technical requirements, the trade, corridor, re post tera measure and the courts. And management requirements in the management of markets in professional. There was only the market in the city pontianak is Flamboyan market which is SNI just the one by the year 2020, while other markets are not qualified. The government of pontianak concentration and focus on market management with a target next year will increase in the Pontianak market with a SNI label. These PKM group followed by 25 participants inculude an academics, students, and representatives of DKUMP, traders and association. Survey results are clustered certified market will next SNI value, representative as Kemuning Market Pontianak because its mostly cleaning market than other, stable inflation and existing fresh market. While the checklist shown as answered 44 items SNI questions which includes the general requirements, technical and management. The results is Kemuning market in IV type of SNI. Discuss and sharing find out that traders blocka are not yet based on SNI measure. There is no disinfectant rooms and water supplies well done yet.